2021
DOI: 10.1186/s12861-021-00243-7
|View full text |Cite
|
Sign up to set email alerts
|

The miR-200 family in normal mammary gland development

Abstract: The miR-200 family of microRNAs plays a significant role in inhibiting mammary tumor growth and progression, and its members are being investigated as therapeutic targets. Additionally, if future studies can prove that miR-200s prevent mammary tumor initiation, the microRNA family could also offer a preventative strategy. Before utilizing miR-200s in a therapeutic setting, understanding how they regulate normal mammary development is necessary. No studies investigating the role of miR-200s in embryonic ductal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 92 publications
1
4
0
Order By: Relevance
“…In fact, adding TGFβ to epithelial cells in culture is a convenient way to induce EMT in various epithelial cells [ 49 ]. Lastly, these data are in line with the high levels of mir200 in late stages of pregnancy in mice [ 50 ].…”
Section: Discussionsupporting
confidence: 77%
“…In fact, adding TGFβ to epithelial cells in culture is a convenient way to induce EMT in various epithelial cells [ 49 ]. Lastly, these data are in line with the high levels of mir200 in late stages of pregnancy in mice [ 50 ].…”
Section: Discussionsupporting
confidence: 77%
“… 256 They play a significant role in inhibiting mammary tumor growth and progression, and their members are being investigated as therapeutic targets. 257 It was also confirmed that miR-200 could suppress the self-renewal and differentiation of CSCs, regulate cell division and apoptosis, and reverse chemotherapy resistance. 258 Additionally, Let7d has been shown to be down-regulated in osteosarcoma CSCs and decrease their sphere- and colony-forming ability.…”
Section: Three Medium Components In the Tumor Microenvironmentmentioning
confidence: 90%
“…The abundance of bta-let-7g-5p increased in EV during H feed restriction (FC = 1.19; P = 0.01); the inhibition role of this miRNA on β-casein protein synthesis and MEC differentiation has also been reported in a mouse model [ 32 ]. Finally, miR-200c-3p , whose abundance increased in EV during H feed restriction (FC = 1.32; P = 0.04), is a member of the miR-200 family and is thus known for its effect on mammary gland morphogenesis [ 33 ]. Its lower abundance during feed restriction was consistent with the reorganization of mammary gland tissue (which could lead to mammary gland involution) that has been observed during an intense feed restriction experiment [ 34 ].…”
Section: Discussionmentioning
confidence: 99%